Potensi Media Sosial dalam Mempopulerkan Konten Sains Islam - Irwandani, Irwandani (Universitas Islam Negeri Raden Intan Lampung, 2016)
The development of internet users in Indonesia is very rapid. In the last five years the number of internet users increased by 430%. By the end of 2015, internet users in Indonesia have reached 88.1 million people. As many as 90% of internet users are social media users. Based on statistical reports there are about 92% of social media users aged between 13-39 years old. That means that there are about 73 million social media users who have the potential to popularize the content of Islamic science in social media. Islamic science was born out of the spirit of Muslim scientists and academics to integrate Islam and science / science. There is some content of Islamic science that can be packed in social media: 1) Content of science in Islam, 2) Content of Muslim inventors 3) Content review of the latest findings in Islamic view, 3) Content wise words of the Scientists.Perkembangan pengguna internet di Indonesia sangat pesat. Dalam lima tahun terakhir jumlah pengguna internet meningkat sebesar 430%. Pada akhir 2015, pengguna internet di Indonesia telah mencapai 88,1 juta orang. Sebanyak 90% pengguna internet adalah pengguna media sosial. Berdasarkan laporan statistik ada sekitar 92% pengguna media sosial berusia antara 13-39 tahun. Itu berarti ada sekitar 73 juta pengguna media sosial yang berpotensi mempopulerkan konten sains Islam di media sosial. Sains Islam lahir dari semangat ilmuwan dan akademisi Muslim untuk mengintegrasikan Islam dan sains/sains. Ada beberapa konten sains Islam yang bisa dikemas dalam media sosial: 1) Konten sains dalam Islam, 2) Konten penemu Muslim 3) Kajian isi temuan terbaru dalam pandangan Islam, 3) Konten kata-kata bijak dari Ilmuwan. Kata kunci: media sosial, sains Islam